2015
DOI: 10.1155/2015/745062
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Immunological Changes in Indian Post Kala-Azar Dermal Leishmaniasis (PKDL) Cases in relation to Treatment: A Retrospective Study

Abstract: Post-kala-azar dermal leishmaniasis (PKDL) is an important factor in kala-azar transmission; hence its early detection and assessment of effective treatment is very important for disease control. In present study on 60 PKDL cases presented with macular, mixed papulonodular, or erythematous lesions, Leishmania parasites were demonstrated microscopically in 91% of papulonodular and 40% of macular lesions. Cellular infiltrates in skin biopsy imprint smears from lesions were mononuclear cells, 25–300/OIF (oil imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…While in hospital-based studies in nonendemic areas a male preponderance (80%) is reported among PKDL patients with a male-to-female ratio of 3–4:1, in endemic areas, the ratio seems much more balanced (ratio 1.2–1.9) and not different from that found in VL [ 10 12 , 14 , 27 29 ].…”
Section: Epidemiologymentioning
confidence: 85%
See 3 more Smart Citations
“…While in hospital-based studies in nonendemic areas a male preponderance (80%) is reported among PKDL patients with a male-to-female ratio of 3–4:1, in endemic areas, the ratio seems much more balanced (ratio 1.2–1.9) and not different from that found in VL [ 10 12 , 14 , 27 29 ].…”
Section: Epidemiologymentioning
confidence: 85%
“…In slit-skin smears, macular lesions will often fail to show parasites, while PN lesions will be positive in 20%–40% [ 13 , 50 ]. The yield is higher in a biopsy (imprint smears): 91% of PN lesions and 40% of macular lesions will show parasites [ 12 ]. Culture and immunohistochemical (IHC) staining improve routine haematoxylin–eosin staining [ 27 ].…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…Both are important opportunistic infections among patients with acquired immunodefi ciency syndrome (AIDS) (14) (15) (16) and have similar clinical presentations, but L. donovani may lead to post-kala-azar dermal leishmaniasis, or infectious skin lesions (17) (18) .…”
Section: Introductionmentioning
confidence: 99%